Teach yourself visually Excel 2007 - Muir, Nancy 1954- (Wiley, 2007)
"Are you a visual learner? Do you prefer instructions that show you how to do something - and skip the long-winded explanations? If so, then this book is for you. Open it up and you'll find clear, step-by-step screen shots that show you how to tackle more than 150 Excel 2007 tasks. Each task-based spread includes easy, visual directions for performing necessary operations ..."--Resource description page
Includes index. - Print version record
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets -- Computer programs; Business -- Computer programs; Tableurs; Logiciels; COMPUTERS; Desktop Applications; Spreadsheets; Business; Computer programs; Electronic spreadsheets; Computer programs